Perangkat Pembelajaran Naskah Drama Untuk Peningkatan Karakter Nilai Budaya - Waraulia, Asri Musandi; Saputro, Agung Nasrulloh (Universitas Hamzanwadi, 2018)
This study aims to process the development of learning tools drama script oriented on the formation of cultural value characters. This development research refers to the Borg and Gall stage model. The stage consists of ten stages of development, namely the initial research and information collection stage, the planning stage, the initial stage of production format development, the initial test phase, the product revision phase, the field test phase, the product revision phase, the field test phase, the product revision phase end, and dissemination and implementation. In this study only until the final product revision stage without including the phase of dissemination and implementation due to limited time research. This research produced Syllabus, RPP, and textbook of drama script oriented to the formation of character of cultural values. The results of this study can be described that the validation of learning devices assessed by two validators, the language validator and graphic design validator. Validation results indicate that the textbooks are included in either category because the percentage is â‰¥ 75%, the initial trial results are trialed in limited to seven junior high school students generated by observation data, interview, and student questionnaire. Observation data can be analyzed that the learning of writing drama script with learning device of drama script oriented to the formation of character of cultural value is successful and the class is very active. Based on interview data submitted by the teacher in a positive way, it can be analyzed that the learning of writing drama script with a drama script-oriented learning tools oriented to the formation of cultural value character is successful. Based on the questionnaire data of students who have a positive opinion, it can be analyzed that the learning of writing drama script oriented on the formation of the character of cultural values is successful.Keywords: development; learning tool; drama script; and cultural values.